The impact of the declaration of the Blue Crab presidium on its value chain in Muisne, Ecuador - Villota, Rafael (2022)
There is currently a distance between consumers and the origin of food products, which translates into the widening of distribution chains and a lack of knowledge of how, where and under what circumstances food is obtained. In order to protect the heritage of localities and create a new rurality, schemes such as Geographical Indications and Slow Food Presidia are created, which seek to revalue and strengthen the value chain for the benefit of all, especially the producing communities. Therefore, the objectives of this research are to analyze the implementation of the Blue Crab Presidium and to measure the impact of the declaration of the Blue Crab Presidium on the value chain in Muisne, Esmeraldas province, Ecuador. The methodology includes a historical analysis of the process of implementing the Blue Crab Presidium through an ethnographic study, review of academic documents and governmental websites. It describes the province of Esmeraldas, the Ingenious Systems of National Agricultural Heritage, the process of recognition of the Blue Crab Presidium, and points out the impact on the value chain of this Presidium and the opportunities for the community, since the harvesting and fattening of blue crab represents one of the major sources of income for the mangrove inhabitants and their future generations.